Efektifitas Metode Tilawati dalam Meningkatkan Kemampuan Membaca Al-Qur’an di SMK Muhammadiyah 1 Prambon Nganjuk - Siti Riadhotun Niful Laily; Nasrul Syarif (PT. Pusmedia Group Indonesia, 2023)
This study discusses the ability to read the Qur'an of students at SMK Muhammadiyah 1 Prambon which is considered lacking by the author. Therefore, the author conducted research by applying the tilawati method to improve the ability to read the Qur'an of students. This type of research is experimental research, which uses two or more groups to serve as the object of study. The first group is the group being studied (experiment) while the second group is the comparison group (control). In this study, researchers conducted a test of question instruments, then tested the validity of both empirical validity tests and expert validity. In the validity test, 13 items were declared valid and 2 items were declared invalid. For 2 invalid questions must be discarded. After 13 questions were declared valid, the researcher conducted a reliability test with the results of 0.751, which is greater than the r table, namely 0.4438, so it can be stated that the question items are reliable. After the pretest was carried out and it was known that the lower average value was the X-TSM 2-TPL class. Then the class was selected as the experimental class, which will be treated with a tilawati method in order to improve the ability to read the Qur'an, and the X-TSM 1 class became the comparison class (control). Before the treatment the average value was 54.63 while after a treatment using the tilawati method, the average post t value increased to 78.57. To determine the difference between the average value between the experimental and control classes after treatment using an independent sample t-test. The paired sample test results showed that the average value of the experimental class was 78.57 while the control class was 65.32. This means that the average value of the experimental class is higher than the average value of the control class. Keywords: Effectivenes; Tilawati Method; Reading The Qur’an.